Superconductivity in layered ZrP2−xSex with PbFCl-type structure. (29th March 2016) - Ishida, Shigeyuki; Fujihisa, Hiroshi; Hase, Izumi; Yanagi, Yousuke; Kawashima, Kenji; Oka, Kunihiko; Gotoh, Yoshito; Yoshida, Yoshiyuki; Iyo, Akira; Eisaki, Hiroshi; Kito, Hijiri
Abstract: We performed a systematic study of the crystal structure, physical properties, and electronic structure of PbFCl-type ZrP2− x Se x (0.3 ≤  x  ≤ 0.9). We successfully synthesized single-phase polycrystalline samples for the Se substitution range of 0.4 ≤  x  ≤ 0.8. The crystal structure of the compound is characterized by the alternate stacking of a two-dimensional P square net and a Zr–(P1− x Se x ) network. ZrP2− x Se x exhibits a dome-like superconductivity phase diagram and has a maximum superconducting transition temperature ( T c ) of 6.3 K for x  ≈ 0.6. Resistivity and Hall measurements indicated that electron–phonon scattering plays a dominant role and that electron-type carriers dominate charge transport. Specific heat measurements confirmed that ZrP2− x Se x exhibits bulk superconductivity. Further, the value of the specific heat jump at T c (Δ C / γT c  ≈ 1.35) is in keeping with the BCS weak-coupling model. These facts suggest a rather conventional pairing mechanism in ZrP2− x Se x . The x dependence of T c can be explained on the basis of the density of states (DOS) for x  ≤ 0.7, whereas the decrease in T c with an increase in the DOS for x  = 0.8 needs further investigation. One possible reason for the suppression of superconductivity is that the PbFCl-type structure becomes unstable for x  ≥ 0.8. The results of electronic structure calculations agree reasonably well with those of the experimental observations, suggesting that the Zr_ d band plays a primary role in determining the physical properties. Further, the calculations predict a significant change in the Fermi-surface topology for x  ≥ 0.8; this is a probable reason for the decrease in T c as well as the instability of the PbFCl-type structure.